Dr. Margarita López-López, Julianne Gavino with students at 2017 SURF Program Reception
SURF students: Krystal Gomez, Yosduan Ramos, and Jennifer Benitez; Assistant Professor of Spanish Dr. Margarita López-López; Julianne Gavino Lecturer of Art; and Provost Dr. Geoff Chase at 2017 SURF Program Reception.